2019
DOI: 10.1117/1.jrs.13.034527
|View full text |Cite
|
Sign up to set email alerts
|

Hyperspectral imaging of minerals in the longwave infrared: the use of laboratory directional-hemispherical reference measurements for field exploration data

Abstract: Hyperspectral imaging (HSI) continues to grow as a method for remote detection of vegetation, materials, minerals, and pure chemicals. We have used a longwave infrared (7.7 to 11.8 μm) imaging spectrometer in a static outdoor experiment to collect HSI data from 24 minerals and background materials to determine the efficacy with which HSI can remotely detect and distinguish both pure minerals and mineral mixtures at a 45-deg tilt angle relative to ground using two different backgrounds. Measurements were obtain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 61 publications
0
15
0
Order By: Relevance
“…9,51 Conclusion Laboratory, industrial, and standoff IR spectroscopies continue their exponential growth. 52,53 It has already been demonstrated 54 that laboratory reference data can readily be used for field detection of both solids and liquids, as well as gases 55 but increasingly the n/k vectors are used for modeling 5,56 the target signal both for liquids 4 and solids. 54 Obtaining n/k for solids is more challenging, and one goal of this study was thus to (determine how to) prepare pellets with high surface smoothness, since the single-angle method measures only specular reflectance.…”
Section: Discussionmentioning
confidence: 99%
“…9,51 Conclusion Laboratory, industrial, and standoff IR spectroscopies continue their exponential growth. 52,53 It has already been demonstrated 54 that laboratory reference data can readily be used for field detection of both solids and liquids, as well as gases 55 but increasingly the n/k vectors are used for modeling 5,56 the target signal both for liquids 4 and solids. 54 Obtaining n/k for solids is more challenging, and one goal of this study was thus to (determine how to) prepare pellets with high surface smoothness, since the single-angle method measures only specular reflectance.…”
Section: Discussionmentioning
confidence: 99%
“…Stand-off detection of chemicals deposited on substrates is an active area of research. [1][2][3][4] These techniques often measure the reflectance in the infrared (IR) spectral region using either passive or active detection. The IR enables higher sensitivity and selectivity due to the natural frequencies of the strong fundamental absorption features for a wide range of species.…”
Section: Introductionmentioning
confidence: 99%
“…This library often incorporates reference spectra that have been measured in a laboratory for the bulk material. 4 However, research has shown that morphological phenomena, e.g., layer thickness, 5 particle size, [6][7][8] etc., can influence the IR reflectance and emission spectra. A single reference spectrum of a pure chemical can thus be insufficient since the material needs to be recorded under similar morphological conditions as the in situ data.…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, the one-step generalized likelihood ratio test has recently been extended for sub-pixel target detection based on the replacement signal model . The sub-pixel target detection is important in many applications, such as battleground reconnaissance (Kumar & Ghosh, 2017), monitoring of mineral material (Myers et al, 2019), and so on.…”
Section: Introductionmentioning
confidence: 99%